Modelling chain for the effect of road traffic on air and water quality: Techniques, current status and future prospects. (February 2015) - Fallah Shorshani, Masoud; André, Michel; Bonhomme, Céline; Seigneur, Christian
Abstract: Modelling approaches for simulating air and stormwater pollution due to on-road vehicles are reviewed and discussed. Models for traffic, emissions, atmospheric dispersion, and stormwater contamination are studied with particular emphasis on their couplings to create a modelling chain. The models must be carefully selected according to the requirements and level of detail of the integrated modelling chain. Although a fair amount of research has been conducted to link air pollution and road traffic, many questions related to spatio-temporal scales, domains of validity, consistency among models, uncertainties of model simulation results, and interfaces between models remain open. The aim of this work is to review the current status of the relationships between traffic, emissions, air quality, and water quality models, to recommend modelling approaches and to propose some directions for improving the state of the science. The difficulties and challenges associated with model coupling are illustrated with specific examples. Highlights: We present a state of the art of traffic, emissions, atmospheric dispersion and stormwater models. We review modelling approaches for simulating air and water pollution with particular emphasis on their couplings. The difficulties and challenges associated with model coupling are discussed with three specific examples. We propose two modelling chains to simulate the environmental impacts of traffic for both average-based and dynamic models.